2009
DOI: 10.1111/j.1540-8159.2009.02520.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcemia Due to Rhabdomyolysis Mimicking Brugada Syndrome

Abstract: We describe a 62-year-old man with a history of multiple myeloma and prostate cancer, presenting with rhabdomyolysis (from a prolonged fall at home), serum calcium 14 mg/dL, and electrocarAddress for reprints: Figure 1. Electrocardiograms at serum calcium levels of: A) 14.0 mg/dl, B) 9.7 mg/dl, and C) 8.8 mg/dl. diogram (ECG) showing coved ST segment elevations in leads V1-V3 typical of Type 1 Brugada syndrome. Hypercalcemia has been reported as a cause of ST elevation mimicking Brugada syndrome. 1-3 There was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
2
7
0
Order By: Relevance
“…[7][8][9] Hypercalcemia was associated with QT interval shortening and delayed cardiac conduction; these ECG changes were restored when serum Ca 2+ levels returned to the normal range. Brugada-type ECG findings have been reported in the right precordial leads in the setting of hypercalcemia, in two case reports, 13,14 and were found in 6% of patients with hypercalcemia in this study. The frequency of J point elevation was not different among causes of hypercalcemia.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…[7][8][9] Hypercalcemia was associated with QT interval shortening and delayed cardiac conduction; these ECG changes were restored when serum Ca 2+ levels returned to the normal range. Brugada-type ECG findings have been reported in the right precordial leads in the setting of hypercalcemia, in two case reports, 13,14 and were found in 6% of patients with hypercalcemia in this study. The frequency of J point elevation was not different among causes of hypercalcemia.…”
Section: Discussionsupporting
confidence: 61%
“…18 In this study, 6% of patients with hypercalcemia exhibited the scooped appearance. Brugada-type ECG findings have been reported in the right precordial leads in the setting of hypercalcemia, in two case reports, 13,14 and were found in 6% of patients with hypercalcemia in this study. Furthermore, this study demonstrated that hypercalcemia was also associated with early repolarization, as was the case in previous case reports.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Thirty‐one cases were identified as meeting our inclusion criteria 72–102 . To confirm these cases as manifestations of Brugada phenocopies, we first sought to assess the clinical probability that the patients had true Brugada syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen cases were included in the metabolic condition category. 72–85 Thirteen patients showed Brugada Type‐1 ECG and five showed Type‐2 ECG. Four of the patients’ ECG switched between a Brugada Type‐1 and a Type‐2 ECG pattern (i.e., had both).…”
Section: Resultsmentioning
confidence: 99%